2005
DOI: 10.1111/j.1365-2567.2005.02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infections in swine induce altered porcine surfactant protein D expression and localization to dendritic cells in bronchial‐associated lymphoid tissue

Abstract: SummarySurfactant protein D (SP-D) is a pattern-recognition molecule of the innate immune system that recognizes various microbial surface-specific carbohydrate and lipid patterns. In vitro data has suggested that this binding may lead to increased microbial association with macrophages and dendritic cells. The aim of the present in vivo study was to study the expression of porcine SP-D (pSP-D) in the lung during different pulmonary bacterial infections, and the effect of the routes of infection on this expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Similar observations in bacterial pneumonia have been reported by several authors [25,27]. Extracellular SP-D content is increased after tracheal inoculation with extraintestinal E. coli (CP9) [25].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Similar observations in bacterial pneumonia have been reported by several authors [25,27]. Extracellular SP-D content is increased after tracheal inoculation with extraintestinal E. coli (CP9) [25].…”
Section: Discussionsupporting
confidence: 78%
“…Extracellular SP-D content is increased after tracheal inoculation with extraintestinal E. coli (CP9) [25]. Increased diffuse porcine SP-D is observed immunohistologically in the surfactant in acute bronchopneumonias caused by A. pleuropneumoniae and Staphylococcus aureus [27]. McIntosh et al demonstrated that SP-D mRNA expression and SP-D protein in BALF were significantly elevated in rats that received intratracheal lipopolysaccharide, which is a component of Gram-negative bacteria [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of pulmonary surfactant protein D (SP-D) was shown as increased during acute and chronic Actinobacillus pleuropneumoniae infection. In that context it was assumed that SP-D could represent a link between the innate and adaptive immune system, facilitating bacterial antigen presentation by dendritic cells in bronchus-associated lymphoid tissue [44].…”
Section: Introductionmentioning
confidence: 99%